The Development of Popular Scientific Book Mangrove Diversity Base on Contextual Learning Material of Biodiversity in Senior High School - Handono, Handono (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
The biology of learning closely related to human life, so that in the learning process process can be implemented in the natural environment, in other words learning not only predicated on the provided text books in school but can also utilize the surrounding environment as a learning resource. Learning that so called contextual learning. One of the environment that can be used as a source for learning is the mangrove. Therefore, the need for innovation learning resource utilization is around students who could potentially be used as an ingredient for the manufacture of learning media for students. In addition to the availability of the media has not discussed the specifics about the mangrove. The media is a popular scientific book on Mangrove Diversity which discusses mangrove diversity that is clearly packaged in an interesting way to overcome the limitations of space and time. This popular scientific book developed to help students better understand about the diversity of mangroves around its environment. This type of research is research development using development model ADDIE. ADDIE development model consists of several stages, namely analysis, design, development, implementation, and evaluation. The subject of the tests in this study consisted of 2 biology teachers and 8 students of class X SMA Maqwa and 2 biology teachers of SMA Maqwa. Data collection instrument on this research is questionnaire. Shape data obtained quantitative data and qualitative data. The results of the validation by an expert of the material retrieved percentage 78.7% with the